ANALYSIS OF URBAN FOREST STRUCTURE, DISTRIBUTION AND AMENITY VALUE: A CASE STUDY - K. F. Akbar; I. Ashraf; S. Shakoor (Journal of Animal and Plant Sciences, 2014)
Trees are an important feature of urban ecosystems and provide different environmental and socio-economic benefits. Different habitats (roadsides, parks, streets, institutes, graveyards) in Sahiwal, a city in central Punjab, Pakistan were surveyed for the assessment of abundance, diversity and amenity value of urban trees. Forty five tree species belonging to 29 families were recorded. Azadirachata indica, Morus alba, Eugenia jambolana and Dalbergia sissoo are the most frequent species. Distribution of trees is highly uneven as only four species showed >50% frequency, seven species had >25% frequency and fourteen species exhibited 5% frequency. Roadside verges had the highest diversity of tree species followed by institutions and parks. Broadleaf deciduous species are abundant whereas conifers and palms are occasionally found in parks and institutions. From a functional point of view, most trees are ornamental type followed by shading trees. Exotic species are higher in number than native species but these are low frequency trees and were mainly found in parks and institutions. Despite higher number of exotic taxa, the number of individual trees belonging to native taxa (56%) was higher than to exotic groups (44%) in the area. Implications for long term tree management and development in Pakistani cities are discussed.
Keywords: Urban trees; urban habitats; diversity of urban trees; amenity value